2005
DOI: 10.1590/s1519-69842005000400008
|View full text |Cite
|
Sign up to set email alerts
|

Applying weight gain in Pomacea lineata (Spix 1824) (Mollusca: Prosobranchia) as a measure of herbicide toxicity

Abstract: Pomacea lineata, an extremely ubiquitous snail and pest to rice farmers throughout Asia, holds promise as a valuable resource for monitoring water quality in northeast Brazil. In this paper, we present data demonstrating the rate of weight gain in P. lineata neonates as a consistent measure of the stress imposed by sublethal concentrations of the herbicides Paraquat and Round-up. Our secondary agenda is to demonstrate the feasibility of incorporating bioassay into the standard municipal and state procedure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Peña and Pocsidio (2007), for example, found that high concentrations of copper can cause a significant retardation in growth of mature P. canaliculata snails and similar results were described for the Florida apple snail, Pomacea paludosa (Hoang et al 2008). Additionally, Coler et al (2005) reported that even after a short exposure, the herbicides Paraquat and Round-up® can also cause a decrease in the growth of the sensitive newly hatched Pomacea lineata snails. In our research the growth and survival of juvenile P. canaliculata snails were assessed after exposure to the water of three streams from basins with different land uses.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Peña and Pocsidio (2007), for example, found that high concentrations of copper can cause a significant retardation in growth of mature P. canaliculata snails and similar results were described for the Florida apple snail, Pomacea paludosa (Hoang et al 2008). Additionally, Coler et al (2005) reported that even after a short exposure, the herbicides Paraquat and Round-up® can also cause a decrease in the growth of the sensitive newly hatched Pomacea lineata snails. In our research the growth and survival of juvenile P. canaliculata snails were assessed after exposure to the water of three streams from basins with different land uses.…”
Section: Introductionsupporting
confidence: 57%
“…The experiments were done with newly hatched snails (0-3 days old) because of their low mortality rate and their potential sensitivity to water pollution (Estebenet & Cazzaniga 1992;Coler et al 2005). The snails were obtained from several egg masses collected at the three streams.…”
Section: Methodsmentioning
confidence: 99%
“…canaliculata that will help to promote different applications of this species, such as its use as a component of high nitrate content in biological fertilizers (Vetayasuporn 2006) or as food for aquaculture (Bombeo-Tuburan et al 1995; Lan et al 2006) and for intensive animal farming (Kaensombath and Ogle 2005). The information obtained here will be also useful to the scheduling of laboratory trials intended for basic research, snail control (Joshi et al 2008; Song et al 2011) or mass rearing for ecotoxicological applications (Lo and Hsieh 2000; Coler et al 2005; Vega et al 2012). …”
Section: Resultsmentioning
confidence: 99%
“…The methodology employed to assay acute and chronic toxicity of Paraquat generally conformed to the appropriate sections listed in Eaton et al (1995). In those instances where they were modified they followed the procedures outline by Buikema et al (1980) for Daphnia similis, Batalla (1997), Melo et al (2000 and Coler et al (2005) for the snail Pomacea lineata, and Aragão et al (1998) and for the prawn Macrobrachium amazonicum.…”
Section: Methodsmentioning
confidence: 99%